2022
DOI: 10.3390/ijerph19159180
|View full text |Cite
|
Sign up to set email alerts
|

Potential Determinants of Cardio-Metabolic Risk among Aboriginal and Torres Strait Islander Children and Adolescents: A Systematic Review

Abstract: Prevention initiatives during childhood and adolescence have great potential to address the health inequities experienced by Aboriginal and Torres Strait Islander (Indigenous) populations in Australia by targeting modifiable risk factors for cardio-metabolic diseases. We aimed to synthesize existing evidence about potential determinants of cardio-metabolic risk markers—obesity, elevated blood pressure, elevated blood glucose, abnormal lipids, or a clustering of these factors known as the metabolic syndrome (Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 94 publications
0
5
0
Order By: Relevance
“…To our knowledge, this is the first systematic review to investigate the prevalence of cardiometabolic risk markers in Aboriginal and Torres Strait Islander young people. This review builds on the findings of a previous publication by our team investigating potential determinants of cardiometabolic risk in this population group [ 52 ]. Our findings suggest that Aboriginal and Torres Strait Islander children have a substantial risk of obesity from early childhood and that the prevalence of obesity increases from childhood into youth, from 10.8% among 2–4-year-olds, compared to 32.1% among 18–24-year-olds, and prevalence of central adiposity of 50.8% among the older age group [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, this is the first systematic review to investigate the prevalence of cardiometabolic risk markers in Aboriginal and Torres Strait Islander young people. This review builds on the findings of a previous publication by our team investigating potential determinants of cardiometabolic risk in this population group [ 52 ]. Our findings suggest that Aboriginal and Torres Strait Islander children have a substantial risk of obesity from early childhood and that the prevalence of obesity increases from childhood into youth, from 10.8% among 2–4-year-olds, compared to 32.1% among 18–24-year-olds, and prevalence of central adiposity of 50.8% among the older age group [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the LSIC, children whose BMI z-score increased at 3-year follow-up were more likely to live in an environment with high financial stress (30.7% vs. 27.4%) and poor diet (33.3% vs. 26.9%) [ 34 ]. However, a recent review of the potential determinants of cardiometabolic risk among Aboriginal and Torres Strait Islander children and youths by McKay et al found that evidence is largely lacking for this population group, and further research is needed, particularly looking at social and environmental factors [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…This review follows the framework of collected articles published between 2001 and 2022 in the form of original research articles, articles with their full text and data available, and studies that explore the pharmacological effects of coumarin in various types of diseases. Following a common search strategy [ 179 ], reference lists of included articles and relevant reviews were searched for any additional publications not captured.…”
Section: Methodsmentioning
confidence: 99%
“…Adolescence is often a period of significant change and an opportunity to develop healthy lifestyle behaviours that may carry into adulthood and contribute to good health [ 2 ]. Physical activity involves body movement that increases energy expenditure, includes different types and contexts such as exercise and sport participation as well as varying frequency, duration and intensity, and has health and wellbeing benefits for adolescents and young people [ 4 , 5 ]. Physical activity has been identified as a priority for holistic health and wellbeing by Aboriginal adolescents and young people [ 6 ].…”
Section: Introductionmentioning
confidence: 99%